Penguatan Pengetahuan Kesiapsiagaan Bencana pada Anak Penyandang Disabilitas Berbasis Aplikasi Sipakdedifa di Kabupaten Klaten - Susilawati, Siti Azizah; Sayekti, Ika Candra; Yuliana, Irma; Hanifa, Muhammad Dzaki; Khotimah, Nur Ahlul; Lestari, Riska Yulia Ayu (Warta LPM, 2025)
Klaten Regency is one of the regencies in Indonesia that has a high risk of natural disasters such as earthquakes, volcanoes, and landslides. People with disabilities are among the groups that are particularly vulnerable to these natural disasters. According to data from Working Group of Special School Principals Klaten Regency, there are five special schools that have been affected by natural disasters, specifically earthquakes, which puts individuals with disabilities at a significant risk of becoming victims. Therefore, it is essential to implement disaster mitigation strategies that involve persons with disabilities as part of disaster risk management. In light of this issue, knowledge transfer related to disaster mitigation is necessary for special school teachers. To enhance effectiveness, technology transfer and the diffusion of science and technology will be based on the SIPAKDEDIFA application. This initiative aims to improve the understanding of Special School Teachers in using the SIPAKDEDIFA application which in turn provides science and technology diffusion to students with disabilities which is expected to optimise students' understanding of disaster mitigation. The methods implemented included socialization, training, technology application, mentoring, and evaluation. The evaluation utilized a pre-test and post-test given to special needs students to assess their understanding of disaster mitigation. The results indicated that special school teachers effectively participated in all activities, and the assistance provided at special school demonstrated that teachers optimally implemented the SIPAKDEDIFA application. The results of the pre-test and post-test to teachers related to knowledge and understanding of the SIPAKDEDIFA application have increased significantly and the results of the pre-test and post-test obtained from students show a very significant increase in the results of knowledge of earthquake, landslide and volcano disaster mitigation with an average score increase of 32.83 points or in percentage of 67.38%. This indicates that the activities had a positive impact on both teachers and special school students in Klaten Regency, ultimately improving disaster mitigation efforts and minimizing losses due to disasters. Based on this research, it is hoped that relevant parties will pay more attention to educating students with disabilities about natural disaster mitigation.